Crossing borders: Body-territory and knowledge production in Randa Maroufi’s Artistic Practice - RHEAMARIADEHNTUTOSAUS (Journal of Global Studies and Contemporary Art)
This paper negotiates entanglements between the Spanish-Moroccan border and the bodies that cross it every day drawing on the artistic practice of Randa Maroufi. I will discuss the border as a dispositive of power that structures the body, its experiences and its boundaries. In doing so, the body is conceived as multi-layered territoriality, at and in which the border interweaves with the flesh. At the same time, the body constitutes the border itself in its daily crossings back and forth. Based on decolonial theoretical thought, with a focus on the cuerpo-territorio approach, I will argue that artistic practice encourages a thinking of the (border) geography taking the body as a starting point. In this way, Maroufi challenges and changes not just geographical knowledge production but also western modern/colonial epistemologies. Art, therefore, becomes as a space for ‘other’ epistemologies.